Serum uric acid: a biochemical prognostic indicator of pregnancy outcomes among pre-eclampsia patients at the federal medical centre, Yenagoa - Obagah, Lukman; Kasia, Benedicta E.; Jeremiah, Israel; Allagoa, Dennis O.; Aigere, Egbaname E. O. S.; Kotingo, Ebikabowei L.; Oriji, Chibuzor P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: High levels of uric acid concentration over normal pregnant values have been reported previously in established preeclampsia, hence it was suggested to be a useful biochemical prognostic marker of the disease. Methods: This is a hospital based prospective case control study where 100 patients with preeclampsia were recruited consecutively as they were admitted. 100 non-pre-eclamptics were also recruited as control. The foetomaternal data, adverse perinatal outcomes, maternal serum uric acid levels as well as complications of preeclampsia were recorded into the protocol. Statistical analysis was done using SPSS 22.0. Level of significance was set at p<0.05. Results: The mean age in the study group was 28±6.7 years while in the control group it was 31±6.5 years. The difference in age was not statistically significant (p=0.53). The mean serum uric acid level was significantly higher amongst participants with preeclampsia than in those without preeclampsia (405.6±995 µmol/L versus 232.7±26.3 µmol/L, p=0.00). Uric acid was statistically associated with the occurrence of eclampsia (p=0.03), Severe hypertension (0.03) and birth asphyxia (p=0.01). Conclusions: The mean serum uric acid was higher in preeclampsia than non-preeclampsia patients. High levels of uric acid were found in eclampsia, severe hypertension and birth asphyxia. However, the prognostic accuracy for uric acid was low for most pregnancy outcomes.